Influence of a twelve-month conditioning program on physical growth, serum hormones, and neuromuscular performance of peripubertal male fencers - Tsolakis, C. K.; Bogdanis, G. C.; Vagenas, G. K.; Dessypris, A. G. (The Journal of Strength and Conditioning Research, 2006)
This study examined the effects of a typical fencing training program on selected hormones, neuromuscular performance, and anthropometric parameters in peripubertal boys. Two sets of measurements, before training and after 12 months of training, were performed on 2 groups of 11- to 13-year-old boys. One group consisted of fencers (n = 8), who trained regularly for the 12-month period, and the other group (n = 8) consisted of inactive children of the same age. There was no difference in Tanner's maturation stage of the 2 groups before (controls, 2.5 +/- 0.3; fencers, 2.1 +/- 0.3) and after the 12 months (controls, 3.0 +/- 0.3; fencers, 3.0 +/- 0.3). Serum testosterone, growth hormone, sex hormone binding globulin, free androgen index, and leptin changed significantly over time, reaching similar values in the 2 groups at the end of the study. Significantly greater increases in body mass (16 +/- 3%) and leg cross-sectional area (CSA) (32 +/- 7%) were observed only in the fencers' group, and these differences disappeared when height was set as a changing covariate. Although there was a greater increase in height for the fencers compared to the control group (8.6 +/- 1.2 vs. 3.6 +/- 0.9 cm, p < 0.01), the height reached at the end of the study was almost identical in the 2 groups (controls, 163.6 +/- 5.1; fencers, 165.4 +/- 2.8). Arm CSA, handgrip strength, and vertical jump performance changed significantly over time for both groups, with no differences between groups. It was concluded that a typical fencing training program for peripubertal boys did not have any effect on selected growth and anabolic hormones and did not influence the normal growth process, as this was reflected by changes in selected anthropometric and neuromuscular performance parameters. This may be because of the characteristics of the present fencing training program, which may not be adequate to alter children's hormonal functions in such a way as to override the rapid changes occurring during puberty.